Situating Salafī Islam in Azerbaijan - Aliyev, Fuad (Die Welt des Islams, 2020)
Salafī daʿwa is a new phenomenon in the religious life of Azerbaijan. Entering the scene in the mid‑1990s as a result of Gulf-funded organizations and the proselytizing activities of foreign students-turned-preachers, Salafīs gradually turned into important actors of Islamic revival in the post-Communist country. Operating in a highly secularized and, moreover, Shīʿī-majority environment, the Salafī daʿwa in Azerbaijan had ex ante limitations that shaped its development patterns. A comprehensive overview of the historical development of the Salafī daʿwa shows that, over three stages, the transnational Salafī movement had become increasingly indigenized. Following these historical observations, the development patterns of the Salafī daʿwa in Azerbaijan are explored, and an attempt is made to explain them through a framework provided by social movement theory. Finally, based on its ideological variations in Azerbaijan, an attempt is undertaken to develop a refined taxonomy of the Salafī movement in this country, based on a critical reassessment of existing classifications.